Adult Lung Spheroid Cells Contain Progenitor Cells and Mediate Regeneration in Rodents With Bleomycin-Induced Pulmonary Fibrosis. (10th September 2015) - Henry, Eric; Cores, Jhon; Hensley, M. Taylor; Anthony, Shirena; Vandergriff, Adam; de Andrade, James B.M.; Allen, Tyler; Caranasos, Thomas G.; Lobo, Leonard J.; Cheng, Ke
Abstract : A rapid and robust method to generate therapeutic resident lung progenitors from adult lung tissues is reported. Outgrowth cells from healthy lung explants were self-aggregated into three-dimensional lung spheroids. Lung spheroid cells inhibited apoptosis, fibrosis, and infiltration but promoted angiogenesis and outperformed adipose-derived mesenchymal stem cells, suggesting that lung spheroids and lung spheroid cells from healthy lung tissues are excellent sources of regenerative lung cells for therapeutic lung regeneration. Abstract: : Lung diseases are devastating conditions and ranked as one of the top five causes of mortality worldwide according to the World Health Organization. Stem cell therapy is a promising strategy for lung regeneration. Previous animal and clinical studies have focused on the use of mesenchymal stem cells (from other parts of the body) for lung regenerative therapies. We report a rapid and robust method to generate therapeutic resident lung progenitors from adult lung tissues. Outgrowth cells from healthy lung tissue explants are self-aggregated into three-dimensional lung spheroids in a suspension culture. Without antigenic sorting, the lung spheroids recapitulate the stem cell niche and contain a natural mixture of lung stem cells and supporting cells. In vitro, lung spheroid cells can be expanded to a large quantity and can form alveoli-like structures and acquire mature lung epithelial phenotypes. In severe combined immunodeficiency mice with bleomycin-induced pulmonary fibrosis, intravenous injection of human lung spheroid cells inhibited apoptosis, fibrosis, and infiltration but promoted angiogenesis. In a syngeneic rat model of pulmonary fibrosis, lung spheroid cells outperformed adipose-derived mesenchymal stem cells in reducing fibrotic thickening and infiltration. Previously, lung spheroid cells (the spheroid model) had only been used to study lung cancer cells. Our data suggest that lung spheroids and lung spheroid cells from healthy lung tissues are excellent sources of regenerative lung cells for therapeutic lung regeneration. Significance: The results from the present study will lead to future human clinical trials using lung stem cell therapies to treat various incurable lung diseases, including pulmonary fibrosis. The data presented here also provide fundamental knowledge regarding how injected stem cells mediate lung repair in pulmonary fibrosis.